DDIS-28. A HIGH THROUGHPUT SCREENING PLATFORM TO IDENTIFY RADIOSENSITIZERS FOR DIPG. (11th November 2019) - Clutter, Matt; Romero, Megan; Becher, Oren
Abstract: Diffuse intrinsic pontine glioma (DIPG) is an incurable brainstem tumor and the leading cause of death in children with brain cancer. Despite numerous clinical trials, no drugs have been found to prolong survival for DIPG patients, suggesting an urgent need to test therapeutics in preclinical models more predictive of clinical activity. To address this gap, we developed a genetically engineered mouse model incorporating the Histone H3.3 K27M mutation, p53 deletion, and PDGFR-α amplification, which co-occur in up to 40% of human DIPG. Here we report the results of a drug screen to identify radiosensitizers of DIPG cells isolated from our mouse model and cultured ex vivo as neurospheres. Although previous clinical trials combining radiotherapy with radiosensitizing agents failed to benefit DIPG patients, they incorporated general radiosensitizers. We hypothesize that searching for radiosynergy using 3-dimensional neurospheres derived from genetically defined primary cell DIPG models will enhance our ability to prioritize clinically relevant radiosensitizers. To identify candidates, we developed high throughput radiation and imaging protocols to quantify the number, size, and viability of neurospheres following treatment. We screened 1, 280 FDA-approved drugs and 1, 600 molecules with a history of clinical use. Two mechanistic classes of compounds were identified that sensitized DIPG neurospheres to radiotherapy, both targeting epigenetic factors. An HDAC1/3 inhibitor along with several different BET bromodomain inhibitors increased cell death 2–3 fold beyond the effect of radiation with minimal activity from the compounds alone. In addition to optimizing the dosing and timing of these compounds for animal studies, we are investigating whether radiosensitization occurs in H3.3 wildtype neurospheres. In the current molecular era of cancer, genetic features like the H3.3 K27M mutation could present an opportunity to develop therapeutics that preferentially radiosensitize diseased cells relative to normal cells. Such "precision radiosensitizers" would advance radiotherapy by enhancing tumor-specific toxicity while sparing bystander cells.